ANALYSIS OF TECHNICAL AND ALLOCATIVE EFFICIENCY OF FARMERS ALONG GINGER VALUE CHAIN IN KADUNA STATE NIGERIA - Alim, S.A.; Murtala, N.; Abdurrahman, S.; Jibril, S.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study analyzed the technical and allocative efficiency of ginger farmers along the value chain in Kaduna State, Nigeria, with a view to identifying productivity gaps and their determinants. A multi-stage sampling technique was used to select 301 ginger farmers across major producing Local Government Areas, and primary data were collected through structured questionnaires during the 2025 production season. Data were analyzed using descriptive statistics, a stochastic frontier production and cost function (Cobb-Douglas specification). The results revealed that, ginger production is predominantly carried out by male (65.4%), middle-aged (mean age = 42.3 years), and experienced farmers (mean farming experience = 17.2 years), operating on small-scale farms (mean size = 1.0 ha) with limited access to extension services (8.31%) and credit (5.32%). The stochastic frontier results showed that, labour (0.4234), seed (0.2567), fertilizer (0.1456), agrochemicals (0.0890) and equipment (0.0456) significantly influenced output at 1% and 5% levels. The gamma value of 0.7234 indicated that 72.34% of output variation was due to technical inefficiency. The mean technical efficiency (TE) was 0.7234, implying a 27.66% output gap, while allocative efficiency (AE) was lower at 0.6456, suggesting a 35.44% cost inefficiency. Determinants of efficiency included age, household size, marital status, education and access to extension services. The study concludes that although farmers are moderately efficient, significant inefficiencies persist, particularly in input allocation, thereby limiting productivity and profitability in ginger production.